The DNA Damage Inducible SOS Response Is a Key Player in the Generation of Bacterial Persister Cells and Population Wide Tolerance - Podlesek, Zdravko; Žgur Bertok, Darja (Frontiers in Microbiology, 2020)
Population wide tolerance and persisters enable susceptible bacterial cells to endure hostile environments including antimicrobial exposure. The SOS response plays a significant role in generation of persister cells, population wide tolerance and shielding. The SOS pathway is an inducible DNA damage repair system that is also pivotal for bacterial adaptation, pathogenesis and diversification. In addition to two key SOS regulators, LexA and RecA, other stressors and stress responses control SOS factors. Bacteria are exposed to DNA damaging agents and other environmental and intracellular factors, including cigarette smoke, that trigger the SOS response at a number of sites within the host. The Escherichia coli TisB/IstR module is as of yet, the only known SOS regulated toxin-antitoxin module involved in persister formation. Nevertheless, the SOS response plays a key role in formation of biofilms that are highly recalcitrant to antimicrobials and can be abundant in persisters. Further the dynamic biofilm environment generates DNA damaging factors that trigger the SOS response within the biofilm, fueling bacterial adaptation and diversification. This review highlights the SOS response in relation to antimicrobial recalcetrance to antimicrobials in four clinically significant species Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Mycobacterium tuberculosis.